if a+b+c = 9 and ab+bc+ca = 23 then a cube + b cube + c cube- 3abc=

Asked by RUDRA YADAV | 15th Sep, 2013, 08:33: PM

Expert Answer:

a3+b3+c3- 3abc = (a+b+c) (a2+b2+c2-ab-bc-ca)

a+b+c= 9 (given)

ab+ bc + ca = 23 (given)

So, a3+b3+c3- 3abc = 9 (a2+b2+c2- 23)            ... (1)

 

(a+b+c)2= a2+b2+c2+ 2ab+ 2bc+ 2ca

92= a2+b2+c2+ 2(ab+bc+ca)

81= a2+b2+c2+ 2(23)

81 = a2+b2+c2+ 46

a2+b2+c2= 35

 

From (1), we get,

a3+b3+c3- 3abc = 9 (35-23) = 108

Answered by  | 15th Sep, 2013, 10:59: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.